A 12‐year survey of methicillin‐resistant Staphylococcus aureus infections in Greece: ST80‐IV epidemic?. (28th April 2014) - Drougka, E.; Foka, A.; Liakopoulos, A.; Doudoulakakis, A.; Jelastopulu, E.; Chini, V.; Spiliopoulou, A.; Levidiotou, S.; Panagea, T.; Vogiatzi, A.; Lebessi, E.; Petinaki, E.; et al.
Abstract Methicillin‐resistant Staphylococcus aureus (MRSA) is an important cause of both healthcare‐associated MRSA (HA‐MRSA) and community‐associated MRSA (CA‐MRSA) infections. Severe MRSA infections have been associated with the virulence factor Panton–Valentine leukocidin (PVL). The aim of this study was to investigate susceptibility patterns, the presence of toxin genes, including that encoding PVL, and clonality among MRSA isolates collected from patients in Greece over a 12‐year period. MRSA isolates were collected from January 2001 to December 2012 from six different hospitals. Antibiotic susceptibility was determined with the disk diffusion method and the Etest. The presence of the toxic shock syndrome toxin‐1 gene (tst), the enterotoxin gene cluster (egc) and the PVL gene was tested with PCR. The genotypic characteristics of the strains were analysed by SCCmec and agr typing, and clonality was determined with pulsed‐field gel electrophoresis and multilocus sequence typing. An increasing rate of MRSA among S. aureus infections was detected up to 2008. The majority of PVL‐positive MRSA isolates belonged to a single clone, sequence type (ST)80‐IV, which was disseminated both in the community and in hospitals, especially during the warmest months of the year. Carriage of tst was associated with ST30‐IV, whereas egc was distributed in different clones. CA‐MRSA isolates were recovered mainly from skin and soft tissue infections, whereas HA‐MRSA isolates were associated with surgical and wound infections. During the period 2001–2012, ST80‐IV predominated in the community and infiltrated the hospital settings in Greece, successfully replacing other PVL‐positive clones. The predominance of ST239‐III in HA‐MRSA infections was constant, whereas new clones have also emerged. Polyclonality was statistically significantly higher among CA‐MRSA isolates and isolates from adult patients.